Analisis Tindak Tutur Ilokusi pada Vlog Jangan Lupa Senyum Part 1 di Kanal Youtube Fiersa Besari - Lana Rahmasari; Asep Purwo Yudi Utomo (Institut Agama Islam Negeri Curup, 2021)
An illocutionary act is a speech act that is usually identified by explicit performative sentences. The research on illocutionary acts in vlogs is an action that shows the meaning of speech during communication. This study aims to describe illocutionary acts on Fiersa Besari's vlog YouTube channel Jangan Lupa Senyum Part 1 along with its speech function. The method used in this research is the descriptive method. The form of research used here is qualitative research. The data source in this study is the vlog Jangan Lupa Senyum Part 1 on the Fiersa Besari YouTube channel. The data in this study are transcripts of conversations between characters in vlogs. Data collection techniques in research using the observation method and note-taking techniques. The findings in the research in this vlog were only 15 utterances of illocutionary speech acts. From the 15 utterances, 7 data on assertive illocutionary acts, 2 directive illocutionary acts, and 7 expressive illocutionary acts. From this research, it is expected that we can understand the function of illocutionary acts that are relevant to everyday life